2022
DOI: 10.1002/prp2.928
|View full text |Cite
|
Sign up to set email alerts
|

The pharmaceutical excipient PEG400 affect the absorption of baicalein in Caco‐2 monolayer model by interacting with UDP‐glucuronosyltransferases and efflux transport proteins

Abstract: The bioavailability of drugs is often related to intestinal metabolism and transport mechanisms. In previous studies, pharmaceutical excipients were recognized as inert substances in clinical safety evaluations. However, a large number of studies have shown that pharmaceutical excipients regulate the metabolism and transport of drugs in the body and improve the bioavailability. The pharmaceutical excipient polyethylene glycol 400 (PEG400) as a good solubilizer and surfactant has the potential to improve the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is suggested that PEG400 may activate the related phase II metabolic enzymes. A previous study by the group showed that PEG400 had a significant promoting effect on UGT1A8 and UGT1A9 [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that PEG400 may activate the related phase II metabolic enzymes. A previous study by the group showed that PEG400 had a significant promoting effect on UGT1A8 and UGT1A9 [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PEG400 alters the systemic exposure of drugs through multiple pathways, such as drug-metabolizing enzymes and transporter functions, affecting cell membrane microenvironments and reversibly opening tight junctions [5][6][7][8][9]. Our previous study also showed that PEG400 could increase the blood concentration and tissue distribution of baicalin by inducing the activities of UGT1A8 and UGT1A9 [10][11][12]. Furthermore, we found that the long-term application of PEG400 as the matrix for TCM soft capsules can cause diarrhea and weight loss in animals, which reminds us to pay attention to the potential impact on healthy bodies.…”
Section: Introductionmentioning
confidence: 90%